Auto-monitoring: theoretical touchstone or circular catch-all? - Nick Hammond (Association for Learning Technology, 1994)
Until I read Ray McAleese's paper, I perhaps had a rather simplistic psychologist's view of concept mapping. It was, I felt, a technique - one of several - that helped learners to articulate their burgeoning understanding of some topic, providing a canvas on which to record, expand and manipulate their knowledge. The activities involved in concept mapping could be linked to well-known psychological principles of understanding, memorization and learning: effort, elaboration and depth of processing; generation and enactment effects; encoding specificity and encoding variability; the distinctions between explicit and implicit representations; metacognitive strategies and reflection, and so forth (Hammond 1993). These psychological underpinnings, while not in any sense providing an integrated 'theory' of concept mapping, give a view of when and why the use of concept mapping might be effective in some situations and not in others, and how different concept mapping tools differ in the claims they are making about their educational use (Trapp, Reader and Hammond 1992).